Ordered Uniform Convexity in Ordered Convex Metric Spaces with an Application to Fixed Point Theory. (6th May 2022) - Beg, Ismat
Abstract : In this paper, we introduce the concept of ordered uniform convexity in ordered convex metric spaces and study some properties of order uniform convexity. Finally, as application, we connect our results with existence of fixed points for monotone non-expansive mappings defined on these spaces.